The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1360-0443.2011.03573.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of a community-based intervention: 5-year follow-up of ‘Clubs against Drugs’

Abstract: The 'Clubs against Drugs' community-based intervention programme, a systems approach to prevention, appears to increase the frequency and effectiveness of club doormen's interventions regarding obviously drug-intoxicated guests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Furthermore, studies have shown that young adults are a high risk-group for drug and alcohol-related problems and this study suggest that one arena where this age group can be reached with preventive measures is at EMDEs. It is important to find settings where emerging adults can be targeted with alcohol and drug prevention programs such as Responsible Beverage Service programs [34-36], and club drug environmental strategies [10,12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have shown that young adults are a high risk-group for drug and alcohol-related problems and this study suggest that one arena where this age group can be reached with preventive measures is at EMDEs. It is important to find settings where emerging adults can be targeted with alcohol and drug prevention programs such as Responsible Beverage Service programs [34-36], and club drug environmental strategies [10,12]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2002, STAD (Stockholm Prevents Alcohol and Drug Problems) initiated a multi-component community-based club drug prevention program, named "Clubs against Drugs". Program evaluations showed an increase in doormen interventions towards drug-intoxicated patrons (e.g., refused entry into the club) [10,11], a decrease in self-reported drug use among staff at licensed premises, and a decrease in staff's observed drug use among patrons [12]. Nevertheless, club drugs at licensed premises remain a major problem in the Swedish nightlife scene, and we are missing information on actual frequency rates of illicit drug use among patrons.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers reported that the community readiness was high and that there was an extensive support for the program [1]. CAD did have an effect on the behaviour of doormen and led to a higher degree of intervention towards apparently drug intoxicated guests [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we have used a methodology where trained actors act out a standardized scene of obvious alcohol intoxication while attempting to purchase alcohol. This methodology is the most widely used, reliable, and time‐efficient with regard to studying serving and security/entry staff behavior and intervention rates toward obviously intoxicated patrons (Buvik and Rossow, ; Gliksman et al., ; Gosselt et al., ; Gripenberg et al., ; Gripenberg‐Abdon et al., ; Hughes et al., ; Rydon et al., ; Toomey et al., ; Wallin et al., , ). Moreover, the methodology has successfully been used to assess overserving at sport stadiums in the United States hosting professional hockey, basketball, baseball, and American football events (Toomey et al., ).…”
mentioning
confidence: 99%